PENGEMBANGAN SOAL MATEMATIKA TIPE PISA DENGAN KONTEKS CABANG OLAHRAGA BULU TANGKIS - DEDI YANSEN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to produce PISA-like math problems with uncertainty and data content in the context of the badminton sport that is valid and practical, as well as to see the potential effect of the questions made on the mathematical literacy skills of class X high school students. The research subjects were students of class X SMA Negeri 3 Prabumulih. The research methodology used is design research with the type of development study, which is divided into 2 stages, those are preliminary and formative evaluation. The preliminary stage includes analysis of research subjects, curriculum, PISA framework, mathematical literacy skills, and making question instruments. The formative evaluation stage includes one to one along with an expert review, then a small group, then a field test. The results of the research data analysis showed that: (1) the PISA-like questions that had been developed were declared valid and practical. Valid based on expert review. Practically based on one to one and small group. (2) PISA-like questions that have been developed have a potential effect on students' mathematical literacy skills. The most widely applied mathematical literacy skills are communication skills. ABSTRAKPenelitian ini bertujuan untuk menghasilkan soal matematika tipe PISA konten uncertainty and data dengan konteks cabang olahraga bulu tangkis yang valid dan praktis, serta melihat efek potensial dari soal yang dibuat terhadap kemampuan literasi matematis siswa kelas X SMA. Subyek penelitian adalah siswa kelas X SMA Negeri 3 Prabumulih. Metodologi penelitian yang digunakan adalah design research dengan tipe development study, yang terbagi menjadi 2 tahap yaitu preliminary dan formative evaluation. Tahap preliminary meliputi analisis subjek penelitian, kurikulum, framework PISA, kemampuan literasi matematis, dan membuat instrumen soal. Tahap formative evaluation meliputi one to one yang bersamaan dengan expert review, selanjutnya small group, kemudian field test. Hasil dari analisis data penelitian diperoleh bahwa: (1) soal-soal tipe PISA yang telah dikembangkan dinyatakan valid dan praktis. Valid berdasarkan pada expert review. Praktis berdasarkan pada one to one dan small group. (2) soal-soal tipe PISA yang telah dikembangkan memiliki efek potensial terhadap kemampuan literasi matematis siswa. Kemampuan literasi matematis yang paling banyak diterapkan yaitu kemampuan komunikasi.